Advancing eco-friendly concrete with locally sourced natural pozzolana - Khushefati, W. H.; Ahmed, Elwy A.; Shihata, A.; Demirboga, Ramazan (Frontiers in Built Environment, 2026)
IntroductionThis study investigates the potential of locally sourced Natural Pozzolana (NP) from Saudi Arabia as a sustainable Supplementary Cementitious Material (SCM) for green concrete, supporting Saudi Vision 2030.MethodsAn extensive experimental program was conducted on nine concrete mixes comprising over 450 specimens, in which Ordinary Portland Cement (OPC) was partially replaced with NP at levels up to 50%, with selected mixes incorporating Silica Fume (SF) and corrosion inhibitors (INH). Fresh properties (slump and initial temperature), mechanical performance (compressive and splitting tensile strength at 7, 28, 56, 90, and 180 days), and durability (chloride permeability and sulphate resistance) were evaluated.ResultsAlthough higher NP contents reduced early-age strength, all NP-based mixes exhibited substantial long-term strength recovery due to sustained pozzolanic activity, with NP20–NP30 achieving 94%–100% of the control strength at 90–180 days. Durability performance improved significantly, with NP mixes reducing chloride permeability by 40%–50%, while SF–NP and INH systems achieved reductions of 70%–76%, shifting RCPT classifications from “moderate” to “very low.” Sulphate exposure produced strength-retention ratios of 100%–114% with no deterioration up to 180 days. One-way ANOVA confirmed that all improvements were statistically significant and attributable to binder composition.Discussion and conclusionsThe findings demonstrate that locally sourced Saudi NP, particularly when combined with SF and corrosion inhibitors, provides a viable pathway for producing durable, low-carbon concrete while reducing cement consumption and supporting sustainable construction practices.